2021
DOI: 10.1149/1945-7111/ac0a21
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Electrodeposition of Copper in the Presence of a Corrosion Reaction

Abstract: This study has examined the pulse electrodeposition of copper from a deep eutectic solvent.Pulse plating parameters were selected using the methodologies originally developed for aqueous solutions, including constraints arising from double layer charging and mass transport effects. Although copper could be deposited under nearly all conditions, in many instances only partial plating was observed and current efficiencies were low. This effect was greatest at low duty cycles and/or when the off-time was long. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…In deriving these expressions, it is assumed that the number of electrons involved in the deposition and dissolution steps are the same. This is normally the case but there are some exceptions, and in previous papers 20,21 a variant of Eq. 2 was used to reflect this.…”
Section: Simplified Corrosion Analysismentioning
confidence: 94%
See 2 more Smart Citations
“…In deriving these expressions, it is assumed that the number of electrons involved in the deposition and dissolution steps are the same. This is normally the case but there are some exceptions, and in previous papers 20,21 a variant of Eq. 2 was used to reflect this.…”
Section: Simplified Corrosion Analysismentioning
confidence: 94%
“…However, some early 6,18 and more recent [19][20][21] studies have shown that it is possible to have corrosion processes occurring during the offtime which can significantly influence deposit properties and current efficiency. This has been observed for the pulse plating of certain metals (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, chemical corrosion is the most established type of corrosion reactions on Li metal anode, which involves the direct redox reactions occurring between Li metal and nonaqueous electrolyte, giving rise to a solid electrolyte interphase (SEI) growth on the Li surface. [ 6a,7 ] This process is spontaneous and ubiquitous during both calendar aging and dynamic electrochemical cycling of Li metal anode. SEI is expected to serve as a passivation layer to kinetically terminate the proliferation of chemical corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…PC mainly used to influence the mechanisms of electrocrystallisation, which in turn control the mechanical and physical properties of the deposited metal 16 , 17 . Since the nucleation rate is proportional to the current density, the use of pulsed single or bipolar currents, which can reach densities significantly higher than their stationary counterparts, can produce deposits with reduced porosity and, a finer grain size 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%